Cellular and molecular mechanisms in kidney fibrosis - Duffield, Jeremy S. (American Society for Clinical Investigation, 2014)
Fibrosis is a characteristic feature of all forms of chronic kidney disease. Deposition of pathological matrix in the interstitial space and within the walls of glomerular capillaries as well as the cellular processes resulting in this deposition are increasingly recognized as important factors amplifying kidney injury and accelerating nephron demise. Recent insights into the cellular and molecular mechanisms of fibrogenesis herald the promise of new therapies to slow kidney disease progression. This review focuses on new findings that enhance understanding of cellular and molecular mechanisms of fibrosis, the characteristics of myofibroblasts, their progenitors, and molecular pathways regulating both fibrogenesis and its resolution.